Differences in the relationship of weight to height, and thus the meaning of BMI, according to age, sex, and birth year cohort. (17th February 2020) - Johnson, William; Norris, Tom; Bann, David; Cameron, Noël; Wells, Jonathan K.; Cole, Tim J.; Hardy, Rebecca
Abstract: Background: Weight can be adjusted for height using the Benn parameter (kg/m B ), where B is the power that minimises the correlation with height. Aim: To investigate how the Benn parameter changes across age (10–65 years) and time (1956–2015) and differs between sexes. Subjects and methods: The sample comprised 49, 717 individuals born in 1946, 1958, 1970 or 2001. Cross-sectional estimates of the Benn parameter were produced and cohort differences at ages 10/11 and 42/43 years were examined using linear regression. Multilevel modelling was used to develop trajectories showing how the Benn parameter changed over age from childhood to mid-adulthood in the three older cohorts. Results: The Benn parameter was closest to 2 in childhood but consistently lower across adulthood, particularly in females and the most recent cohort. At ages 10/11 years, the Benn parameter was greater than 3 in both sexes in the 2001 cohort but between 2.2 and 2.7 in the three older cohorts. This difference was estimated to be +0.67 (0.53, 0.81) in males and +0.53 (0.38, 0.68) in females, compared to the 1946 cohort, and was driven by a much higher weight SD in the 2001 cohort. Conversely, at ages 42/43 years, the Benn parameter was lowest in the 1970 cohort due to a slightly lower weight-height correlation. This difference was estimated to be −0.12 (−0.34, 0.10) in males and −0.15 (−0.42, 0.13) in females, compared to the 1946 cohort. Conclusions: Changes over time in the obesogenic environment appear to have firstly reduced the Benn parameter due to a lowering of the weight-height correlation but secondly and more drastically increased the Benn parameter due to increasing weight variation.